2020
DOI: 10.1097/jcp.0000000000001183
|View full text |Cite
|
Sign up to set email alerts
|

A 12-Week Randomized, Double-Blind, Placebo-Controlled Clinical Trial of Topiramate for the Treatment of Compulsive Buying Disorder

Abstract: Background Topiramate is an anticonvulsant that has shown promise as a pharmacological agent for the treatment of addictive disorders, including compulsive buying disorder (CBD). The aim of the present study was to examine the efficacy of topiramate in the treatment of CBD and its associated characteristics using a 12-week randomized, double-blind, placebo-controlled design. Methods Fifty patients seeking treatment of CBD who met the inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The superiority of topiramate vs. placebo was not confirmed by the main outcome measure (YBOCS-SV), and only clinical variables (hoarding, impulsivity) and Compulsive Buying Follow-Up Scale (CB-FUS) scores confirmed the efficacy of topiramate vs. placebo ( 56 ). However, the follow-up analysis suggested that topiramate may begin to distinguish itself from placebo after 10 weeks, which indicates the need for a longer duration of monitoring ( 56 ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The superiority of topiramate vs. placebo was not confirmed by the main outcome measure (YBOCS-SV), and only clinical variables (hoarding, impulsivity) and Compulsive Buying Follow-Up Scale (CB-FUS) scores confirmed the efficacy of topiramate vs. placebo ( 56 ). However, the follow-up analysis suggested that topiramate may begin to distinguish itself from placebo after 10 weeks, which indicates the need for a longer duration of monitoring ( 56 ).…”
Section: Resultsmentioning
confidence: 93%
“…A randomized, double-blind, controlled trial evaluated the efficacy of topiramate (up to 300 mg/day in the ninth week, if tolerated) vs. placebo for 12 weeks in 50 patients with B/SD ( 56 ). The superiority of topiramate vs. placebo was not confirmed by the main outcome measure (YBOCS-SV), and only clinical variables (hoarding, impulsivity) and Compulsive Buying Follow-Up Scale (CB-FUS) scores confirmed the efficacy of topiramate vs. placebo ( 56 ). However, the follow-up analysis suggested that topiramate may begin to distinguish itself from placebo after 10 weeks, which indicates the need for a longer duration of monitoring ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified six psychotherapy studies, two of those were open trials ( Filomensky & Tavares, 2009 ; Granero et al., 2017 ) and four were randomized controlled studies ( Benson, Eisenach, Abrams, & van Stolk-Cooke, 2014 ; Mitchell, Burgard, Faber, Crosby, & de Zwaan, 2006 ; Müller, Arikian, de Zwaan, & Mitchell, 2013 ; Müller, Mueller, et al., 2008 ). In terms of the seven included pharmacological studies, two were open studies ( Grant, Odlaug, Mooney, O'Brien, & Kim, 2012 ; Koran, Bullock, Hartston, Elliott, & D'Andrea, 2002 ), another two started with an open-label phase that was followed by a double-blind discontinuation phase ( Koran, Aboujaoude, Solvason, Gamel, & Smith, 2007 ; Koran, Chuong, Bullock, & Smith, 2003 ), and three studies had a clear placebo-controlled design ( Black, Gabel, Hansen, & Schlosser, 2000 ; Nicoli de Mattos et al., 2020 ; Ninan et al., 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the 13 identified studies were conducted in the United States ( Benson et al., 2014 ; Black et al., 2000 ; Grant et al., 2012 ; Koran et al., 2002 , 2003 , 2007 ; Mitchell et al., 2006 ; Müller et al., 2013 ; Ninan et al., 2000 ). Two studies were performed in Brazil ( Filomensky & Tavares, 2009 ; Nicoli de Mattos et al., 2020 ) and one study each in Germany ( Müller, Mueller, et al., 2008 ) and Spain ( Granero et al., 2017 ). Within all studies, mean ages of participants ranged between 24.0 and 46.55 years, and the vast majority of participants were women (range 72–100%).…”
Section: Resultsmentioning
confidence: 99%
“…There is no compelling evidence that addiction treatments are effective for compulsive buying (Criterion 4). Cognitive-behaviour therapy, naltrexone and topiramate are not more effective than placebo, nor are tricyclic and SSRI antidepressants; although they are effective for mood symptoms (Hague, Hall, & Kellett, 2016;Kellett, Oxborough, & Gaskell, 2021;Nicoli de Mattos et al, 2020). However, existing studies tend to be of low methodological quality.…”
Section: Candidate Behavioural Addictionsmentioning
confidence: 99%